Analysis of tourism carrying capacity as a strategy for sustainable birdwatching tourism management - Betancur-Rodríguez, Víctor H. (2022)
Objective: to determine the tourist carrying capacity through the analysis of the current concept; identifying the necessary propositions and explaining the sufficient meaning for the strategic management of sustainable and sustainable avitourism in Colombia, which has an important potential for diversification. Method. The methodology of documentary analysis and the technique of tracking, indexing, annotation, extraction, organization, translation and systematization of reviews of articles and electronic documents were applied, establishing the convergences and divergences of the theoretical and methodological constructs assumed in the ways of understanding, describing and evaluating the tourist carrying capacity of avitourism. Results: In the literature reviewed, the most referenced theoretical and conceptual approaches to tourism carrying capacity applied to avitourism are identified, as well as some of the scopes and limitations of the methodological models used and an approach to the analysis of this method from a multidisciplinary perspective. Conclusion. It concludes with the determination of the key and essential elements that should be present in the tourist carrying capacity as a tool for the management of sustainable bird watching tourism.